Monetary policy shocks, financial constraints and firm-level equity return: panel evidence - Zulkefly Abdul Karim; Mohd. Azlan Shah Zaidi; Bakri Abdul Karim (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present paper investigates the effect of monetary policy shocks upon the equity returns of financially constrained and less-constrained firms in Malaysia for the 1990-2008 period using firm-level data. Monetary policy shocks are generated via a recursive structural VAR (SVAR) identification scheme that allows the monetary authority to set the overnight interbank rate after observing the current value of world oil price, foreign income, foreign monetary policy, domestic output and inflation. The Malaysian firms examined are divided into two categories based upon the cash flow to income ratio, namely financially constrained and financially less-constrained. After augmenting the Fama and French (1992, 1996) multifactor model using a dynamic panel data approach, the results reveal that equity returns of financially constrained firms are more affected by domestic monetary policy than the returns of less constrained firms. Meanwhile, international monetary policy shocks significantly influence the equity returns of financially less-constrained firms, but not those of financially constrained firms.